3D Impulse Response Measurements of Spaces Using an Inexpensive Microphone Array. Issue 2 (June 2013) - Protheroe, Daniel; Guillemin, Bernard
The acoustical characteristics of a room are traditionally determined using omnidirectional impulse response measurements, yielding information about sound reflections in terms of magnitude and time, but not direction. However, the direction of reflections is often important, and thus the need for a practical, low cost measurement system for determining this. In this paper we present the performance of a low cost measurement system utilising an inexpensive microphone array, namely the Core Sound TetraMic, for the determination of 3D room impulse responses. These can then be visualised, for example, as a "hedgehog pattern". Experiments undertaken in an anechoic chamber indicate that the accuracy of directional estimation of this system is in the region of ±7.5°.